2013
DOI: 10.1002/rcm.6546
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive low‐pressure dielectric barrier discharge ion source

Abstract: LP-DBDI is a soft ionization method characterized by only minor fragmentation, similar to APCI. The sensitivity of the LP-DBDI source was found to be about 40 times higher than that of the conventional APCI source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We previously developed a highly sensitive ionization source, the LP-DBDI source, whose optimum pressure is around several thousand Pa . It is shown schematically in Figure C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously developed a highly sensitive ionization source, the LP-DBDI source, whose optimum pressure is around several thousand Pa . It is shown schematically in Figure C.…”
Section: Resultsmentioning
confidence: 99%
“…21 With a commercial mass spectrometer (DS1000, Hitachi, Ltd., Tokyo, Japan), we confirmed that a ■ RESULTS AND DISCUSSION Discontinous Sample Gas Introduction and Low-Pressure Dielectric Barrier Discharge. We previously developed a highly sensitive ionization source, the LP-DBDI source, whose optimum pressure is around several thousand Pa. 18 It is shown schematically in Figure 1C. Even when an ion trap was used for the mass analyzer, the pressure of the chamber in which the ion trap was located had to be around 0.1 Pa to obtain unit mass resolution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the discharge sources like glow or barrier discharge are more easily stabilized under reduced pressure. 33,34) Due to the high surface tension of water (0.073 N/m), spraying of pure aqueous solution is known to have higher ESI onset voltage compared to organic solvent mixtures (e.g. 50 v/v% methanol/water solution).…”
Section: Electrospray Under Super-atmospher Ic Pressure Esi and Dischmentioning
confidence: 99%
“…Our group developed a prototype of a portable mass spectrometer for use in the screening of illicit drugs as an alternative to an immunoassay kit. 18,19) It uses a highly sensitive ionization source, a low-pressure dielectric barrier discharge ionization (LP-DBDI) source. A discontinuous sample gas introduction technique and a vacuum headspace method are used to e ciently transport the sample vapor to the LP-DBDI source.…”
Section: Introductionmentioning
confidence: 99%